Analysis on the Absolute Growth Rate of Rhizophora mucronata Seedling in Silvicultural Pond Canals by the Influence of Initial Condition and Changes of Environment Quality - Hastuti, Endah Dwi; Budihastuti, Rini (Biosaintifika: Journal of Biology & Biology Education, 2016)
Mangrove seedling growth in silvofishery pond is limited to water quality dynamics while the water quality dynamically changes. This research aimed to study the changes of environmental factor condition in silvofishery pond and to analyze its impacts on the growth of mangrove seedling. Research experiment involved18 treatment plots with mangrove Rhizophora mucronata seedling. Observed parameters included temperature, turbidity, salinity, pH, DO, TSS, BO, N and P. Calculation was conducted for the deviation of each parameters. Mangrove growth parameters were including height and diameter growth while its data processing was absolute daily growth. Data analysis was conducted through regression. The result showed there were changes on environment parameters. Growth rate of R. mucronata showed variations on absolute daily height growth rate range of 0.215-3.333 mm/day (average 1.296 0.036 mm/day), while absolute daily diameter growth rate range was 2.15x10-3-0.196 mm/day (average 4.25x10-2 3.59x10-2 mm/day). The analysis of regression showed several parameters effectedthe growth of mangrove seedlings including temperature, temperature change, turbidty, salinity change, pH, pH change, and DO on the growth of R. mucronata seedlings. This research concluded that environment parameters and its changes had significant effects on the growth of mangrove seedling. How to CiteHastuti, E., & Budihastuti, R. (2016). Analysis on the Absolute Growth Rate of Rhizophora mucronata Seedling in Silvicultural Pond Canals by the Influence of Initial Condition and Changes of Environment Quality. Biosaintifika: Journal of Biology & Biology Education, 8(1), 56-63.